Plant protection praxis on Hévíz Nature Conservation Area (Lake Balaton District, Hungary) - Bürgés, György; Németh, György (Acta Agraria Debreceniensis, 2015)
The nature conservation park, which belongs to the Spa and St. Andrew Hospital for Rheumatics of Hévíz, is 60 ha in size. The famous Lake of Hévíz, the two overfalls and the main buildings of the hospital are located in the middle of the park. They are surrounded by protective forests, parks and gravel esplanades. During the past few decades, the population of neophyton plants and invasive insects have increased considerably. These mean serious challanges to develop efficient control methods. Special care must be taken of environmental and plant protection regulations. Keeping plant protective regulations are especially strict around natural and spa waters.